2011
DOI: 10.1136/annrheumdis-2011-200372
|View full text |Cite
|
Sign up to set email alerts
|

Leptin produced by joint white adipose tissue induces cartilage degradation via upregulation and activation of matrix metalloproteinases

Abstract: Leptin acts as a pro-inflammatory adipokine with a catabolic role on cartilage metabolism via the upregulation of proteolytic enzymes and acts synergistically with other pro-inflammatory stimuli. This suggests that the infrapatellar fat pad and other WAT in arthritic joints are local producers of leptin, which may contribute to the inflammatory and degenerative processes in cartilage catabolism, providing a mechanistic link between obesity and osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
1
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 52 publications
5
168
1
6
Order By: Relevance
“…Interestingly, leptin secretion was 40 % lower and adiponectin was increased by 70 % in IPFP cells compared with the subcutaneous adipose tissue [73]. Moreover, it was demonstrated that the culture media from OA patients' IPFP adipocytes induced MMP13 and MMP1 expression in articular chondrocytes and that the leptin level positively correlated with the expression of both MMPs and cartilage collagen destruction [20]. The end-stage OA patients' fat pad cells also showed an increased expression of inflammatory cytokines and down-regulation of anabolic peptides, such as VCAM1 (vascular cell adhesion molecule-1), CTGF (connective tissue growth factor) and CD44 (cluster of differentiation) [74].…”
Section: Adipocytokines Secretion By Infrapatellar Fat Padmentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, leptin secretion was 40 % lower and adiponectin was increased by 70 % in IPFP cells compared with the subcutaneous adipose tissue [73]. Moreover, it was demonstrated that the culture media from OA patients' IPFP adipocytes induced MMP13 and MMP1 expression in articular chondrocytes and that the leptin level positively correlated with the expression of both MMPs and cartilage collagen destruction [20]. The end-stage OA patients' fat pad cells also showed an increased expression of inflammatory cytokines and down-regulation of anabolic peptides, such as VCAM1 (vascular cell adhesion molecule-1), CTGF (connective tissue growth factor) and CD44 (cluster of differentiation) [74].…”
Section: Adipocytokines Secretion By Infrapatellar Fat Padmentioning
confidence: 84%
“…These proteins have been detected in synovial fluid (SF) and the plasma of patients with OA [16][17][18]. A putative source of adipocytokine secretion in the region of the knee joint is the infrapatellar fat pad (IPFP) [19,20]. In addition, recent findings indicate that deteriorated articular cartilage is another source of adipocytokines within the joint [21].…”
Section: Introductionmentioning
confidence: 99%
“…24 25 In a recent in vitro study, leptin, either alone or in synergy with interleukin 1, significantly induced collagen release from cartilage by upregulating collagenolytic and gelatinolytic activity. 26 Some preliminary epidemiological studies have suggested a potential role of circulating leptin in OA. While Iwamoto reported that serum leptin concentration might be related to increases in body weight and total fat mass in postmenopausal women with knee OA, 27 Miller reported that decreases in serum leptin could explain why weight loss improved physical function and symptoms in patients with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings showed that leptin might play a positively protective role against the destructive course of arthritis. However, Hui et al [110] found that leptin coming from joint white adipose tissue could trigger cartilage degradation by promoting and activating the matrix metalloproteinases. Leptin served as a proinflammatory adipokine with a catabolic role on cartilage metabolism by raising proteolytic enzymes and working synergistically with other proinflammatory stimuli.…”
Section: Cellular Studies Concerning the Effect Of Leptin On Cartilagementioning
confidence: 99%